2002
DOI: 10.1016/s0886-3350(01)01235-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic phacoemulsification using a 1.4 mm incision: Clinical results

Abstract: A sleeveless phaco tip was used to perform successful bimanual phacoemulsification using conventional phaco machines and familiar surgical techniques. The cataracts were safely removed through an incision of 1.4 mm or smaller that was widened for IOL insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
1
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 5 publications
4
73
1
1
Order By: Relevance
“…We have modified microsurgical instruments like the irrigating chopper and keratome to perform phaconit surgery through 0.9 mm incision and implant specially designed rollable IOL (thinopt X Rollable lens) through a 1.2-1.3 mm incision. Bimanual phacoaspiration and phacofragmentation achieved minimal phaco-power ranging from 5-30% (average 10-15%) as compared to standard phacoemulsification (30-50% phaco power) effective irrigation and aspiration time of 30-150 seconds, vacuum setting of 100-150mm Hg during fragment emulsification and 450 mmHg during cortical clean up similar to other studies [4][5][6][7][8]. The energy requirement and fluids can be monitored effectively with the help of advanced phacosystems [10] using burst mode technology, however we used basic Venturi system.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We have modified microsurgical instruments like the irrigating chopper and keratome to perform phaconit surgery through 0.9 mm incision and implant specially designed rollable IOL (thinopt X Rollable lens) through a 1.2-1.3 mm incision. Bimanual phacoaspiration and phacofragmentation achieved minimal phaco-power ranging from 5-30% (average 10-15%) as compared to standard phacoemulsification (30-50% phaco power) effective irrigation and aspiration time of 30-150 seconds, vacuum setting of 100-150mm Hg during fragment emulsification and 450 mmHg during cortical clean up similar to other studies [4][5][6][7][8]. The energy requirement and fluids can be monitored effectively with the help of advanced phacosystems [10] using burst mode technology, however we used basic Venturi system.…”
Section: Discussionsupporting
confidence: 78%
“…The energy requirement and fluids can be monitored effectively with the help of advanced phacosystems [10] using burst mode technology, however we used basic Venturi system. We had higher incidence of chamber instability and other intraoperative complications like minimal corneal burn (2.5% cases) as compared to other studies [3,[7][8][9][10]. In our view, this increased incidence was not due to smaller bore irrigating chopper and micro flow 0.9 mm phacotip but the initial learning curve, as intraoperative complications decreased in subsequent cases.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…[1][2][3][4] In addition, surgery can be performed through incisions of 1.4 mm, [5][6] or even through a 0.9 mm incision, 1 hence inducing less postsurgery astigmatism than conventional coaxial phacoemulsification (CP). [5][6] It is well recognized that in CP, temporal clear corneal incisions (CCI) induce the least astigmatism. The ophthalmic literature estimates that the magnitude of surgically induced astigmatism (SIA) studied by vector analysis is around 0.44 D and 0.88 D, rising as the size of the incision increases.…”
Section: Introductionmentioning
confidence: 99%
“…Sleeveless bimanual microincision cataract surgery (MICS), as reported by Alio, 1,2 Agarwal, 3,4 or Tsuneoka, 5,6 employs an irrigation chopper, a sleeveless tip, and the bimanual phaco technique, which is supposed to be safer and less invasive than the conventional coaxial phaco method. A 2004 survey by the American Society of Cataract and Refractive Surgery indicated that 40% of eye surgeons in the United States planned to use the bimanual microincision phaco technique.…”
Section: Introductionmentioning
confidence: 99%